2011
DOI: 10.1016/j.ijgo.2010.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Task shifting and sharing in Tigray, Ethiopia, to achieve comprehensive emergency obstetric care

Abstract: Not only do NPCs perform a significant proportion of emergency obstetric procedures in Tigray, but the postoperative outcomes achieved under their care are similar to those attained by physicians. Strengthening NPC training programs in emergency obstetric surgery should further reduce maternal and fetal mortality and morbidity in Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 17 publications
4
74
1
1
Order By: Relevance
“…In task shifting or task sharing, it is assumed that with adequate training, the less specialized health workers can provide competent services. Therefore these methods are in the interest of most systems to address their human resource shortage (2,6,8) which experienced for example in providing HIV/AIDS care (9,10), mental healthcare (11), family planning (12) and obstetric care (13). This approach also is applied in maternity care in which midwife tasks are moved to lay health workers (14).…”
Section: Key Messagesmentioning
confidence: 99%
“…In task shifting or task sharing, it is assumed that with adequate training, the less specialized health workers can provide competent services. Therefore these methods are in the interest of most systems to address their human resource shortage (2,6,8) which experienced for example in providing HIV/AIDS care (9,10), mental healthcare (11), family planning (12) and obstetric care (13). This approach also is applied in maternity care in which midwife tasks are moved to lay health workers (14).…”
Section: Key Messagesmentioning
confidence: 99%
“…• on-off payments to cover costs of transport to hospital, 32,46 • task-shifting policies in which non-physician clinicians are trained to perform a significant proportion of emergency obstetric procedures with similar post-operative outcomes to physicians, as in programmes in Mozambique, Tanzania, Malawi and India, 47,48 • use of radio-telephones or solar-powered VHF radio communication systems, which have reduced transport delays and improved communication and access to information and advice between, for example, general practitioners and traditional birth attendants, and women patients and health services, 49 • geographic information systems, designed to work with all types of geographically referenced data, used to trace geographic difficulties in reaching emergency obstetric care, 50 and…”
Section: Interventions Based On the Frameworkmentioning
confidence: 99%
“…16 Studies assessing outcomes of emergency obstetric surgery have shown that trained non-clinicians have as good results as trained clinicians. 17,18 Surgery and the global health agenda Outside of obstetrics and gynaecology, NPCs have also been trained in provision of orthopaedic care. For example, in Malawi, Orthopaedic Clinical Officers have been trained since 1985 in the conservative management of common traumatic and non-traumatic conditions.…”
Section: Task Shifting/task Sharingmentioning
confidence: 99%